Self-Care and Unpleasant Symptoms in Indonesian Postpartum Mothers with Twin Babies: a Case Report - Lina Ayu Marcelina; Imami Nur Rachmawati; Wiwit Kurniawati (Universitas Malahayati Lampung, 2023)
ABSTRACT Postpartum mothers with twin babies are in a critical condition in terms of maternal health because of their need to adapt to the presence of two babies at once. To describe nursing processes in five cases of postpartum mothers with twin babies. We reported nursing processes in five cases of postpartum mothers with twin babies, addressing the nursing care and self-care applied and referring to the theory of unpleasant symptoms. The five mothers presented to two hospitals in Jakarta, Indonesia. During three days of treatment, the postpartum mothers were able to perform regular self-care without assistance, even though their self-management and time management were not optimal. However, they suffered unpleasant symptoms, including postpartum discomfort, breast engorgement, lack of support from husbands, and anxiety. Interventions were conducted via relaxation techniques, lactation management, and health education related to maternal and infant care for twin babies, together with family involvement and the provision of support from health-care providers and assistants. Time and self-management skills in postpartum mothers with twin babies need to be strengthened. Health-care providers are recommended to facilitate family assistance while the mother is in the hospital postpartum ward and to provide home visits as a form of follow-up. Keywords: Postpartum, Self-Care, Twin Babies, Unpleasant Symptoms